Effects of microstructural tailoring on Na storage performance of graphene - Yao, Li‐Hua; Zhao, Jian‐Guo; Li, Jing‐Wei (International journal of quantum chemistry, 2021)
We probe the effects of microstructural tailoring on Na storage performance of graphene by using the density functional theory (DFT). The results indicate that four types of graphenes with microstructural tailoring, that is, B‐doped‐graphene (B‐graphene), O‐doped‐graphene (O‐graphene), vacancy graphene (V‐graphene) and pyrrolic graphene (D‐graphene) exhibit improved Na storage performance involve adsorption energy, theoretical specific capacity, electronic structure and average potentials. These four types of graphenes exhibit reduced adsorption energies of −3.250, −4.347, −2.666, and −4.531 eV, and increased theoretical specific capacities of 634, 683, 720, and 720 mA h/g, respectively. Graphene with microstructural tailoring by N doping (N‐graphene) shows a poor Na storage performance (the adsorption energy is −1.161 eV and the theoretical specific capacity is 275 mA h/g). This is due to the strong interactions between B‐graphene, O‐graphene, V‐graphene, and D‐graphene and Na, which can be rationalized by the observed orbital hybridizations. The results suggest that the four types of microstructural tailoring (B‐graphene, O‐graphene, V‐graphene, and D‐graphene) are expected to improve the Na storage performance of graphene. Energy storage is of great significance to the world socio‐economic development and environmental protection and has become growing global concerns over the world. Microstructural tailoring changes the electronic structure of material, thereby determining its properties. This provides an insight into future challenges and guidelines for finding next‐generation energy storage materials and promotes the scientific and technological revolution as well as industrial revolution in the new era.